Respon Petani Terhadap Pemberian Ekstrak Daun Kelor (Moringa Oleifera) Pada Air Minum Broiler - M, Mihrani; Siradjuddin, Sri Nurhikmah (Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the administration farmer respon of Moringa Leaf Extract in Drinking Water on Abdominal Fat and Broiler Blood Cholesterol. The counseling was held at the Tappakodong Farmers Group, Bungaejaya Village, Palangga District, Gowa Regency in June 2022. Data analysis showed that the administration of Moringa leaf extract in drinking water on abdominal fat and blood cholesterol the best is giving 30ml/l. Effectiveness of counseling carried out in the Tappakodong Farmers Group, Bungaejaya Village, Palangga District, Gowa Regency, with the effectiveness of counseling the percentage of knowledge 64.17%, attitudes 74.81% and skills 79.33% which means that the response of the Tappakodong Farmer Group is good to the material presented .